Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Gula Aren di Desa Jambi Tulo Kecamatan Maro Sebo Provinsi Jambi - Marwoto, Marwoto; Nurmansah, Rahmad; Sitorus, Arta Sari (Jurnal MeA (Media Agribisnis), 2025)
Palm sugar is one of the NTFP derivative products from sugar palm that is most widely cultivated by Villagers, including in Jambi Tulo Village, in Jambi Province. There are three ways that can be used by KTH Aren Serbaguna members in marketing their output, namely: self-marketing, retailers and collectors which cause differences in the selling prices received by farmers. This research aims to: 1) Identify and analyze the Marketing Mix carried out by palm sugar farmers who market themselves, retailers and collectors 2) Analyze internal and external factors in marketing palm sugar which is marketed by themselves, through retailers and collectors 3) Formulate appropriate marketing strategy in marketing palm sugar which is marketed by itself, through retailers and through collectors. The research method used is a combination of qualitative and quantitative data analysis. Data collection techniques will be carried out through interviews, questionnaires, observations, literature studies and documentation. With a total of 27 respondents determined by purposive sampling.The results of the study showed that marketing channel 0 (farmers-consumers) is more profitable. In addition, the strategy of channel 0 (farmers-consumers) is in quadrant II while marketing channels 1 and 2 are both in quadrant III.